Working Capital Management of Selected Power Sector Companies in Bangladesh: Evidence from Dhaka Stock Exchange Ltd. - Islam, Md. Nazrul; Mili, Shamem Ara (Asian Business Review, 2018)
The present study is an attempt to explore the existing working capital management practices of the 3 (three) selected power sector companies listed in Dhaka Exchange Ltd. of Bangladesh. The study covered a period of 6 (six) years from 2010 to 2015. The basic sources of the collected secondary financial data are the DSE archive, published annual reports, and official websites of the selected companies. The study adopted quick ratio, cash to current liability, inventory turnover, receivable turnover, and cash conversion cycle as working capital management indicators of the sample companies. Through descriptive statistics, the study found that the working capital management practices over the study period of the selected companies are satisfactory though there is a scope to invest from the excess working capital in profitable investment opportunities. Student’s t-test and ANOVA technique showed that the differences among the working capital management practices of the sample companies over the study period are significant concerning all the selected working capital ratios except inventory turnover.